2016
DOI: 10.7554/elife.12089
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory polymorphisms modulate the expression of HLA class II molecules and promote autoimmunity

Abstract: Targeted sequencing of sixteen SLE risk loci among 1349 Caucasian cases and controls produced a comprehensive dataset of the variations causing susceptibility to systemic lupus erythematosus (SLE). Two independent disease association signals in the HLA-D region identified two regulatory regions containing 3562 polymorphisms that modified thirty-seven transcription factor binding sites. These extensive functional variations are a new and potent facet of HLA polymorphism. Variations modifying the consensus bindi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
105
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(110 citation statements)
references
References 138 publications
4
105
0
Order By: Relevance
“…This effect of Stat4 may be independent of its roles in promoting IFN-γ production, although further studies are needed to confirm this. Recent data show that a lupus-associated SNP in the STAT4 gene leads to increased Stat4 expression (114), supporting the idea that higher Stat4 expression may promote autoimmunity. Interestingly, knockout of the Stat4 gene reduces autoantibody production in lupus-prone B6.TC mice (115).…”
Section: Discussionmentioning
confidence: 75%
“…This effect of Stat4 may be independent of its roles in promoting IFN-γ production, although further studies are needed to confirm this. Recent data show that a lupus-associated SNP in the STAT4 gene leads to increased Stat4 expression (114), supporting the idea that higher Stat4 expression may promote autoimmunity. Interestingly, knockout of the Stat4 gene reduces autoantibody production in lupus-prone B6.TC mice (115).…”
Section: Discussionmentioning
confidence: 75%
“…Differential HLA expression levels have been associated with infectious (6063), autoimmune and inflammatory (61, 6467) disease outcome. Our data indicate that alternative polyadenylation is one mechanism by which HLA-A cell surface expression levels are regulated, potentially affecting HLA-A-mediated immune responses.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have indicated that expression levels of certain HLA loci vary in an allotype dependent manner (416) and this variation has been shown to associate with certain diseases, such as outcome after HIV infection (4, 17), Crohn’s disease (4), HBV clearance (8), graft-versus-host disease after unrelated hematopoietic cell transplantation (18, 19), Parkinson’s disease (20), systemic lupus erythematosus (21) and certain cancers (22–24). The regulation of HLA class I expression is mediated by a series of core promoter motifs, which are located within 500 bp upstream of the start site and are relatively conserved (25).…”
Section: Introductionmentioning
confidence: 99%